Kala Pather Poisoning and Liver Function Tests in Children (Medical Forum Monthly, 2020)
Objective: To Study the Kala Pather Poisoning and Liver Function Tests in Children.Study Design: Experimental studyPlace and Duration of Study: This study was conducted in ICU of Children Hospital Lahore during Jan 2014 to Jan 2019.Materials and Methods: This study was performed in ICU of Children Hospital Lahore. Fifty-two patients with Paraphenylenediamine (PPD) poisoning who came to emergency from 2014 to 2019 were included in it. History was recorded and physical examination was done. All cases were of accidental poisoning. Both males and females were included. Their age was less than 9 years. LFTs were measured. Intubation, tracheostomy and ventilators were needed for proper management.Results: Maximum level of serum bilirubin, AST and ALT was 3 mg/dl, 760 mg/dl and 784 mg/dl respectively. All the patients showed abnormal LFTs. 77% were intubated, 42% needed tracheotomy and 65% needed ventilator. Only one child died so survival of cases was 96%. Manner of poisoning was accidental in all cases.Conclusion: Paraphenylenediamine poisoning is fatal one. But if properly managed with tracheostomy or ventilators the mortality can be very much reduced.